MEDIA IN CRISIS SITUATIONS – SOCIO-PSYCHOLOGICAL CONSEQUENCES AND RECOMMENDATIONS (Heritage, 2025)
During social crises, people have an increased need to be informed about events in the social environment, which directs them to the media, much more than to primary groups. Such a social context gives the media a great possibility of manipulation aimed at the affective and cognitive dimensions of personality. The significant role of the media has been confirmed in the new generation of conflicts, such as information and biological wars. Expert analyzes of media coverage in developed countries during the COVID-19 pandemic showed that the authorities in Europe and the USA were in some ways the biggest producers of disturbing news that caused fear and anxiety among citizens with the possible goals of nation-states to achieve the desired shock through media coverage. - effect on the population due to accelerated immunization of citizens. Researches in the country and the region indicated that: a higher level of information leads to a higher level of anxiety, that the media is a source of frustration and that moderation in their use is necessary. Crisis communication has shown its shortcomings, which can lead to psychological and economic consequences. In crisis situations, a person experiences changes in the value system, moral reasoning, attitudes towards God and religion, attitude towards death, development of circadian rhythms and changes in smoking and alcohol consumption habits. Propaganda, rumours, misinformation as means of informational and psychological action, which are known in the military framework, during crisis situations have spread to the civilian world, which is just getting to know their devastating effects on people and groups. All of the above points to the necessity of improving the concept of psychological defense at the social and personal level by improving defense strategies and educating the population.
Keywords: KOVID19, media, information, consequences, recommendations